Hubungan Antara C-Reactive Protein dengan Mortalitas dan Lama Rawat Pasien COVID-19 di RSUP Dr. Sardjito - Ramsi, Irhash Faisal; Widyastuti, Yunita; Widodo, Untung (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: COVID 19 is an emerging viral infectious disease that is currently spreading around the world, and has become a pandemic. Diverse clinical manifestations also produce extensive morbidity and mortality. C reactive protein (CRP) is a new biomarker that describe the event of inflammation or infection. Serum CRP level reflects the relationship with disease severity and high mortality. Objective: The objective of this study is to analyze the relationship between CRP level and patient’s length of stay and mortality. Method: This study used retrospective observational cohort method at the Medical Records and Accounting Departement, Dr. Sardjito Hospital by reviewing confirmed COVID 19 patient’s medical records examined serum CRP level in the period of April until December 2020. To analyze the relationship between CRP level and mortality, logistic regression was used. And to analyze to relationship between CRP level and hospital length of stay, Kaplan-Meier was used. Result: Total sample population was 285 patients, and 178 patients met inclusion and exclusion criteria. The median of age of the patients was 54 years old (19-89) consist of 60,7% male patients and 39,3% female patients. Subjects with higher CRP level (>72 mg/L) were at higher risk of death (HR 4,726; p< 0,001) than those with lower CRP level. The difference in LOS was significantly different between groups of subjects, with the median LOS for subjects with CRP >72 mg/L was 20 days, while for subjects with CRP ≤72 mg/L was 16 days (p= 0.021). Conclusion: Increased serum CRP level >72 mg/L strongly related with increased risk of mortality and length of hospital stay in COVID-19 patients.